ANALISIS FAKTOR YANG MEMPENGARUHI PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Nurita Budi Pratiwi; Rustam Hanafi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
SAK ETAP is a one DSAK efforts to facilitate SMEs in preparing financial statements and to resolve its internal problem. SAK ETAP made not as complete as GAAP. However, until now the application of IFRSs ETAP is still very low. SAK ETAP still burdensome SMEs, the cause of SMEs still do not know the importance of making financial reports, the lack of knowledge of the owner of the accounting, and etc. So the purpose of this study is to analyze the factors that affect the implementation of ETAP SAK on SMEs. This study used a sample of 64 SMEs spread Area Tegal. The variables of this research is the application of IFRSs ETAP as the dependent variable, while the owner of education, understanding of Information Technology, the qualitative characteristics of financialstatements and the size of the business as an independent variable. Data were analyzed using linear regression technique. The results of this study identify that education owner, understanding of Information Technology, the qualitative characteristics of financial statements and the size of the business and significant positive effect on the implementation of ETAP SAK on SMEs. This means that the higher education owner, understanding of Information Technology, the qualitative characteristics of financial statement report and the size of the business, the better the application of IFRSs ETAP .